2020
DOI: 10.1016/j.pocean.2020.102371
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in physiology and shell condition of the pteropod Limacina retroversa in the Gulf of Maine relative to life cycle and carbonate chemistry

Abstract: Natural cycles in the seawater partial pressure of carbon dioxide (CO2) in the Gulf of Maine, which vary from ~250-550 µatm seasonally, provide an opportunity to observe how the life cycle and phenology of the shelled pteropod Limacina retroversa responds to changing food, temperature and carbonate chemistry conditions. Distributional, hydrographic, and physiological sampling suggest that pteropod populations are located in the upper portion of the water column (0-150 m) with a maximum abundance above 50 m, al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(49 citation statements)
references
References 84 publications
3
23
0
Order By: Relevance
“…Here, geneexpression analysis showed that genes linked to calcification were upregulated, presumably to counter a further reduction of the calcification rate. A similar finding was recorded for natural populations of North Atlantic L. retroversa, where lower shell condition and upregulation of biomineralization genes was found in response to seasonally lower Ar state (Maas et al, 2020). Hence, lower shell weight of sub-Antarctic L. retroversa in near-future conditions likely indicates that the organisms are less able to maintain calcification rates when exposed to more acidified conditions.…”
Section: Changing Shell Propertiessupporting
confidence: 81%
See 1 more Smart Citation
“…Here, geneexpression analysis showed that genes linked to calcification were upregulated, presumably to counter a further reduction of the calcification rate. A similar finding was recorded for natural populations of North Atlantic L. retroversa, where lower shell condition and upregulation of biomineralization genes was found in response to seasonally lower Ar state (Maas et al, 2020). Hence, lower shell weight of sub-Antarctic L. retroversa in near-future conditions likely indicates that the organisms are less able to maintain calcification rates when exposed to more acidified conditions.…”
Section: Changing Shell Propertiessupporting
confidence: 81%
“…The first generation is produced in austral spring, when a rapid increase in size is essential to reach fertility and produce offspring for the second generation in late summer (Dadon and de Cidre, 1992;Seibel et al, 2007). The same applies to L. retroversa in the Gulf of Maine, where the phytoplankton spring bloom is thought to enable rapid growth of the juvenile pteropods (Maas et al, 2020). We mimicked a scenario of high food abundance in our experiments, by successfully feeding the incubated pteropods with microalgae (as shown by bright-green stomach contents and mucous webs) and all pteropods were still swimming lively after 3 days.…”
Section: Changing Shell Propertiesmentioning
confidence: 99%
“…If atlantids reach reproductive maturity in approximately 116 days, this could allow for more than one generation per year. This is comparable to the shelled pteropods, which are thought to live for approximately 1-2 years and may produce two generations of offspring per year in the Southern Ocean [96,97], and in more temperate waters [98]. During specimen collection in the South Atlantic Ocean for the present study, small juvenile and large adult specimens were present in the same location at the same time, supporting this inference.…”
Section: A Complex Response To Oasupporting
confidence: 80%
“…Pteropod shells are made of a more soluble calcium carbonate compound (aragonite) than the form used by most planktonic species, and are impacted at a higher saturation state (ΩAr =1.5) than would be predicted from pure chemical equilibrium (ΩAr =1.0), the point at which aragonite is predicted to dissolve (Bednarsek et al, 2019), suggesting that their shell condition could serve as an "early warning" of OA impacts for other shelled species. Natural phenology and seasonal cycles have, however, been demonstrated to influence phenotypic responses of thecosomes to OA (León et al, 2020;Maas et al, 2020), confounding and potentially obscuring the correlations between saturation state and the gene expression, respiration, and shell condition of these potential bioindicators. A metanalysis of the response metrics was only able to find consensus on thresholds of response (Bednarsek et al, 2019), rather than develop consistent predictive relationships between saturation state and a response variable.…”
Section: Introductionmentioning
confidence: 99%